2021
DOI: 10.3389/fonc.2021.671548
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanisms of Pristimerin in Cancer Therapy: Recent Advances

Abstract: Seeking an efficient and safe approach to eliminate tumors is a common goal of medical fields. Over these years, traditional Chinese medicine has attracted growing attention in cancer treatment due to its long history. Pristimerin is a naturally occurring quinone methide triterpenoid used in traditional Chinese medicine to treat various cancers. Recent studies have identified alterations in cellular events and molecular signaling targets of cancer cells under pristimerin treatment. Pristimerin induces cell cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 144 publications
(330 reference statements)
0
20
0
1
Order By: Relevance
“…Studies have reported that PRI can inhibit migration and invasion of various tumor cells [ 14 , 19 ], including NSCLC cells [ 40 ]. The effects of F@FPP on A549 cell migration was tested by using scratch test and Transwell system, and it was indicated that the migration capacity of tumor cells with treatment of P@FPP NMs was obviously inhibited compared to the PRI combined with PTX administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that PRI can inhibit migration and invasion of various tumor cells [ 14 , 19 ], including NSCLC cells [ 40 ]. The effects of F@FPP on A549 cell migration was tested by using scratch test and Transwell system, and it was indicated that the migration capacity of tumor cells with treatment of P@FPP NMs was obviously inhibited compared to the PRI combined with PTX administration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese traditional herbs play an auxiliary anti-cancer role by inducing cell apoptosis, enhancing immune system function, and reversing multiple drug resistance [ 10 , 11 ]. As a natural quinonemethide triterpenoid isolated from celastraceae and hippocrateaceae , pristimerin (PRI) possess multiple pharmacological activities of anti-tumor, anti-inflammatory, and anti-oxidation [ 12 14 ]. Studies have shown that PRI exhibits inhibitory effects on a variety of tumors, including lung cancer [ 15 , 16 ], breast cancer [ 17 , 18 ], and colorectal cancer [ 19 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that PRI can inhibit migration and invasion of various tumor cells [14,19], including NSCLC cells [35]. The effects of F@FPP on A549 cell migration was tested by using scratch test and Transwell system, and it was indicated that the migration capacity of tumor cells with treatment of P@FPP NMs was obviously inhibited compared to the PRI combined with PTX administration (Fig.…”
Section: Cell Viability and Metastasis Inhibition Of P@fpp Nms In Vitromentioning
confidence: 96%
“…Chinese traditional herbs play an auxiliary anti-cancer role by inducing cell apoptosis, enhancing immune system function, and reversing multiple drug resistance [10,11]. As a natural quinonemethide triterpenoid isolated from celastraceae and hippocrateaceae, pristimerin (PRI) possess multiple pharmacological activities of anti-tumor, anti-in ammatory, and anti-oxidation [12][13][14]. Studies have shown that PRI exhibit inhibitory effects on a variety of tumors, including lung cancer [15,16], breast cancer [17,18], and colorectal cancer [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Since its isolation in 1951 and structural elucidation in 1954, different biological activities have been attributed to pristimerin (Kulkarni and Shah, 1954). Among these activities are anti-inflammatory (Kim, Park and Kim, 2013;Zhao et al, 2020), antioxidant (Shaaban et al, 2018), antimalarial (Figueiredo et al, 1998), antibacterial (López, de León and Moujir, 2011), and anti-tumor (Yousef et al, 2016;Yousef et al, 2017;Lee et al, 2018;Cevatemre, et al, 2018;Zhao et al, 2019;Li et al, 2019;Chen et al, 2021;Al-Tamimi et al, 2022). The cytotoxic activity observed in several tumor lines was related to the fact that pristimerin presents antiproliferative activity involving apoptosis or programmed cell death (Li et al, 2019), autophagy (Cevatemre, et al, 2018), and inhibition of signaling pathways such as nuclear factor Kappa B (NF-κB) (Tu et al, 2018), Akt (kinase protein B, PKB) (Park and Kim, 2018), modulation of MAPK signaling pathways (Al-Tamimi et al, 2022), among others.…”
Section: Introductionmentioning
confidence: 99%